2022
DOI: 10.2166/wcc.2022.433
|View full text |Cite
|
Sign up to set email alerts
|

Soil loss estimation and prioritization using geographic information systems and the RUSLE model: a case study of the Anger River sub-basin, Western Ethiopia

Abstract: Soil erosion is a major environmental problem that affects people's livelihoods and environmental health, particularly in developing countries. The present study aimed to identify soil erosion hotspot areas and prioritization in the Anger River Sub-basin for conservation planning. The Revised Universal Soil Loss Equation model and geospatial technologies were adopted to identify soil erosion hotspot areas and prioritization of the sub-watershed for conservation planning. Key parameters such as rainfall data, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…A research study conducted by Ref. [ 5 ] in the Anger River sub-basin showed that approximately 43.6% and 8.4% of soil loss were very severe and severe, respectively. A similar study also conducted by Ref.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A research study conducted by Ref. [ 5 ] in the Anger River sub-basin showed that approximately 43.6% and 8.4% of soil loss were very severe and severe, respectively. A similar study also conducted by Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In emerging nations like Ethiopia, where agriculture is the foundation of the economy, this issue is especially prominent [ 3 ]. According to rural land use systems, problems of soil disintegration, sedimentation, and cleaning in a certain part of Ethiopia are a chronic environmental problem [ [4] , [5] , [6] ]. In several highlands of Ethiopia, agricultural expansion and intensification, urbanization, and the extraction of timber and other distinctive resources will likely accelerate over the course of the foreseeable future in order to meet demand in the highland of Ethiopia [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations